Practitioners' perception toward AIS course content offered by Malaysian universities - Ismail, Noor Azizi; Abdullah, Akilah; Kamardin, Hasnah (Universiti Utara Malaysia, 1999)
The purpose this study is to determine the degree of importance of each topic included in the Accounting Information System (AIS) course from the practitioners' point of views. This study was motivated by the increasing progress in information technology which proposed to re-examine the AIS course in order to meet the expectations and requirements of the profession. Three hundred and forty (340) questionnaires were sent to there different groups of companies namely public accounting firms, industry and commerce, and banking and finance. The response rate received is 22.35%. Respondents' opionions on the importance od AIS topics were measured using of five-point Likert Scale.